Intraoperative Perfusion Assessment in Mastectomy Skin Flaps: How Close are We to Preventing Complications? - Khavanin, Nima; Qiu, Cecil; Darrach, Halley; Kraenzlin, Franca; Kokosis, George; Han, Tinglu; Sacks, Justin M. (Journal of Reconstructive Microsurgery, 2019)
Background Mastectomy flap necrosis is the source of considerable morbidity and cost following breast reconstruction. A great deal of effort has been put forth to predicting and even preventing its incidence intraoperatively.Methods A review of the literature was performed evaluating the evidence of mastectomy skin flap perfusion technologies.Results Multiple technologies have leveraged spectroscopy and/or angiography to provide real-time assessment of flap perfusion, including indocyanine green, fluorescein, and light-based devices.Conclusion This manuscript endeavors to review the evidence on mastectomy skin flap perfusion analysis, highlighting the benefits, and downsides of the current technologies and identifying exciting areas of future research and development.
Keywords: necrosis; perfusion; prevention; flap; technology